name | base |
version | 1.0 |
description | The standard theory library |
author | Joe Hurd <joe@gilith.com> |
license | MIT |
show | Data.Bool Data.List Data.Option Data.Pair Data.Sum Data.Unit Function Number.Natural Number.Numeral Relation |
⊦ ∀t. (λx. t x) = t
⊦ ∃f. injective f ∧ ¬surjective f
⊦ ∀P x. P x ⇒ P ((select) P)
⊦ T
⊦ wellFounded (<)
⊦ wellFounded (λx y. F)
⊦ id = λx. x
⊦ pre 0 = 0
⊦ map id = id
⊦ ∀x. x = x
⊦ ∀v. v = ()
⊦ ∀n. 0 ≤ n
⊦ ∀n. n ≤ n
⊦ ∀m. wellFounded (measure m)
⊦ F ⇔ ∀p. p
⊦ ∀l. all (λx. T) l
⊦ let = λf x. f x
⊦ 1 = suc 0
⊦ ∀x. id x = x
⊦ ∀t. t ∨ ¬t
⊦ ∀n. ¬(n < n)
⊦ ∀n. 0 < factorial n
⊦ ∀n. 0 < suc n
⊦ (¬) = λp. p ⇒ F
⊦ (∃) = λP. P ((select) P)
⊦ ∀a. ∃x. x = a
⊦ ∀a. ∃!x. x = a
⊦ ∀t. (∀x. t) ⇔ t
⊦ ∀t. (∃x. t) ⇔ t
⊦ ∀t. (λx. t x) = t
⊦ ∀f g. f = g
⊦ T ⇔ (λp. p) = λp. p
⊦ (∀) = λP. P = λx. T
⊦ ∀a'. ¬(none = some a')
⊦ ∀x. destLeft (left x) = x
⊦ ∀x. x = x ⇔ T
⊦ ∀y. destRight (right y) = y
⊦ ∀n. ¬(factorial n = 0)
⊦ ∀n. ¬(suc n = 0)
⊦ ∀n. n ≤ n * n
⊦ ∀n. even n ∨ odd n
⊦ ∀n. 1 ≤ factorial n
⊦ ∀n. pre (suc n) = n
⊦ ∀m. m * 0 = 0
⊦ ∀m. m + 0 = m
⊦ ∀n. n - n = 0
⊦ ∀l. reverse (reverse l) = l
⊦ ∀l. l @ [] = l
⊦ ∀e. ∃fn. fn () = e
⊦ ∀e. ∃!fn. fn () = e
⊦ ∀l. map (λx. x) l = l
⊦ 2 = suc 1
⊦ ∀t1 t2. (λx. t1) t2 = t1
⊦ ∀n. ¬(even n ∧ odd n)
⊦ ∀n. even (2 * n)
⊦ ∀n. bit0 n = n + n
⊦ ∀n. bit1 n = suc (bit0 n)
⊦ ∀n. ¬even n ⇔ odd n
⊦ ∀n. ¬odd n ⇔ even n
⊦ ∀n. n div 1 = n
⊦ ∀n. exp n 1 = n
⊦ ∀n. n mod 1 = 0
⊦ ∀l. null l ⇔ l = []
⊦ ∀l. drop (length l) l = []
⊦ ∀l. take (length l) l = l
⊦ ∀x. (select y. y = x) = x
⊦ ∀m n. m ≤ m + n
⊦ ∀m n. n ≤ m + n
⊦ ∀P. P () ⇒ ∀x. P x
⊦ (⇒) = λp q. p ∧ q ⇔ p
⊦ ∀t. (t ⇔ T) ∨ (t ⇔ F)
⊦ ∀n. odd (suc (2 * n))
⊦ ∀m. suc m = m + 1
⊦ ∀n. bit1 n = suc (n + n)
⊦ ∀n. exp 1 n = 1
⊦ ∀n. suc n - 1 = n
⊦ ∀l. null (concat l) ⇔ all null l
⊦ ∀x. (fst x, snd x) = x
⊦ ∀x y. fst (x, y) = x
⊦ ∀x y. snd (x, y) = y
⊦ ∀h t. ¬(h :: t = [])
⊦ ∀h t. tail (h :: t) = t
⊦ ∀b t. (if b then t else t) = t
⊦ ∀n x. length (replicate n x) = n
⊦ ∀m n. length (interval m n) = n
⊦ ∀t h. head (h :: t) = h
⊦ ∀P x. P x ⇒ P ((select) P)
⊦ (¬T ⇔ F) ∧ (¬F ⇔ T)
⊦ ∀n. 0 < n ⇔ ¬(n = 0)
⊦ ∀l. length l = 0 ⇔ l = []
⊦ ∀f y. (λx. f x) y = f y
⊦ ∀p. ∃x y. p = (x, y)
⊦ ∀x y. x = y ⇔ y = x
⊦ ∀x y. x = y ⇒ y = x
⊦ ∀t1 t2. t1 ∧ t2 ⇔ t2 ∧ t1
⊦ ∀t1 t2. t1 ∨ t2 ⇔ t2 ∨ t1
⊦ ∀a b. (a ⇔ b) ⇒ a ⇒ b
⊦ ∀n m. m > n ⇔ n < m
⊦ ∀n m. m ≥ n ⇔ n ≤ m
⊦ ∀m n. m * n = n * m
⊦ ∀m n. m + n = n + m
⊦ ∀m n. m = n ⇒ m ≤ n
⊦ ∀m n. m < n ⇒ m ≤ n
⊦ ∀m n. m < n ∨ n ≤ m
⊦ ∀m n. m ≤ n ∨ n < m
⊦ ∀m n. m ≤ n ∨ n ≤ m
⊦ ∀m n. m - (m + n) = 0
⊦ ∀m n. n - (m + n) = 0
⊦ ∀m n. m + n - m = n
⊦ ∀m n. m + n - n = m
⊦ ∀m n. n * (m div n) ≤ m
⊦ ∀l f. length (map f l) = length l
⊦ ∀<< x. wellFounded << ⇒ ¬<< x x
⊦ ∀n. exp n 2 = n * n
⊦ ∀n. 2 * n = n + n
⊦ ∀m. measure m = λx y. m x < m y
⊦ ∀f g. (f o g) = λx. f (g x)
⊦ ∀m n. ¬(m < n ∧ n < m)
⊦ ∀m n. ¬(m < n ∧ n ≤ m)
⊦ ∀m n. ¬(m ≤ n ∧ n < m)
⊦ ∀m n. ¬(m < n) ⇔ n ≤ m
⊦ ∀m n. ¬(m ≤ n) ⇔ n < m
⊦ ∀m n. m < suc n ⇔ m ≤ n
⊦ ∀m n. suc m ≤ n ⇔ m < n
⊦ ∀m. m = 0 ∨ ∃n. m = suc n
⊦ ∀x. x = none ∨ ∃a. x = some a
⊦ ∀P. (∀b. P b) ⇔ P T ∧ P F
⊦ ∀P. (∃b. P b) ⇔ P T ∨ P F
⊦ ∀P. P F ∧ P T ⇒ ∀x. P x
⊦ (∧) = λp q. (λf. f p q) = λf. f T T
⊦ ∀n. even n ⇔ n mod 2 = 0
⊦ ∀n. ¬(n = 0) ⇒ 0 div n = 0
⊦ ∀n. ¬(n = 0) ⇒ 0 mod n = 0
⊦ ∀f. surjective f ⇔ ∀y. ∃x. y = f x
⊦ ∀P. (∀x. ¬P x) ⇔ ¬∃x. P x
⊦ ∀P. (∃x. ¬P x) ⇔ ¬∀x. P x
⊦ ∀P. ¬(∀x. P x) ⇔ ∃x. ¬P x
⊦ ∀P. ¬(∃x. P x) ⇔ ∀x. ¬P x
⊦ (∃) = λP. ∀q. (∀x. P x ⇒ q) ⇒ q
⊦ ∀a a'. some a = some a' ⇔ a = a'
⊦ ∀A B. (B ⇒ A) ⇒ ¬A ⇒ ¬B
⊦ ∀t1 t2. ¬(t1 ⇒ t2) ⇔ t1 ∧ ¬t2
⊦ ∀t1 t2. ¬t1 ⇒ ¬t2 ⇔ t2 ⇒ t1
⊦ ∀m n. m < n ⇒ m div n = 0
⊦ ∀m n. m < n ⇒ m mod n = m
⊦ ∀m n. m ≤ n ⇒ factorial m ≤ factorial n
⊦ ∀m n. m + suc n = suc (m + n)
⊦ ∀m n. m < m + n ⇔ 0 < n
⊦ ∀m n. n < m + n ⇔ 0 < m
⊦ ∀m n. suc m = suc n ⇔ m = n
⊦ ∀m n. suc m < suc n ⇔ m < n
⊦ ∀m n. suc m ≤ suc n ⇔ m ≤ n
⊦ ∀m n. m + n = m ⇔ n = 0
⊦ ∀m n. m + n = n ⇔ m = 0
⊦ ∀m n. m - n = 0 ⇔ m ≤ n
⊦ ∀m n. pre (suc m - n) = m - n
⊦ ∀m n. suc m - suc n = m - n
⊦ ∀f l. map f l = [] ⇔ l = []
⊦ ∀n. odd n ⇔ n mod 2 = 1
⊦ ∀n. exp 0 n = (if n = 0 then 1 else 0)
⊦ ∀n. ¬(n = 0) ⇒ n div n = 1
⊦ ∀m. 0 - m = 0 ∧ m - 0 = m
⊦ ∀f. (id o f) = f ∧ (f o id) = f
⊦ ∀f g x. (f o g) x = f (g x)
⊦ ∀m n. max m n = (if m ≤ n then n else m)
⊦ ∀m n. min m n = (if m ≤ n then m else n)
⊦ ∀m n. even (m * n) ⇔ even m ∨ even n
⊦ ∀m n. even (m + n) ⇔ even m ⇔ even n
⊦ ∀m n. odd (m * n) ⇔ odd m ∧ odd n
⊦ ∀m n. m * suc n = m + m * n
⊦ ∀m n. ¬(n = 0) ⇒ m mod n < n
⊦ ∀m n. ¬(n = 0) ⇒ m div n ≤ m
⊦ ∀m n. ¬(n = 0) ⇒ m mod n ≤ m
⊦ ∀n. even n ⇔ ∃m. n = 2 * m
⊦ ∀l n. n < length l ⇒ member (nth n l) l
⊦ ∀l m. null (l @ m) ⇔ null l ∧ null m
⊦ ∀l m. length (l @ m) = length l + length m
⊦ ∀l m. reverse (l @ m) = reverse m @ reverse l
⊦ ∀<< m. wellFounded << ⇒ wellFounded (λx x'. << (m x) (m x'))
⊦ ∀P. (∀x y. P (x, y)) ⇒ ∀p. P p
⊦ ∀P. (∀p. P p) ⇔ ∀p1 p2. P (p1, p2)
⊦ ∀P. (∃p. P p) ⇔ ∃p1 p2. P (p1, p2)
⊦ ∀a b. ∃f. f F = a ∧ f T = b
⊦ ∀m n. m ≤ n ⇔ ∃d. n = m + d
⊦ ∀x. x = [] ∨ ∃a0 a1. x = a0 :: a1
⊦ ∀P a. (∀x. a = x ⇒ P x) ⇔ P a
⊦ ∀P l. ¬exists P l ⇔ all (λx. ¬P x) l
⊦ ∀P l. ¬all P l ⇔ exists (λx. ¬P x) l
⊦ ∀f g. f = g ⇔ ∀x. f x = g x
⊦ ∀f g. (∀x. f x = g x) ⇒ f = g
⊦ ∀P a. (∀x. x = a ⇒ P x) ⇔ P a
⊦ ∀P a. (∃x. a = x ∧ P x) ⇔ P a
⊦ ∀P a. (∃x. x = a ∧ P x) ⇔ P a
⊦ ∀P. P none ∧ (∀a. P (some a)) ⇒ ∀x. P x
⊦ (∨) = λp q. ∀r. (p ⇒ r) ⇒ (q ⇒ r) ⇒ r
⊦ (even 0 ⇔ T) ∧ ∀n. even (suc n) ⇔ ¬even n
⊦ (odd 0 ⇔ F) ∧ ∀n. odd (suc n) ⇔ ¬odd n
⊦ ∀m n. m ≤ n ⇔ m < n ∨ m = n
⊦ ∀m n. n ≤ m ⇒ m - n + n = m
⊦ ∀m n. m < n ∨ n < m ∨ m = n
⊦ ∀m n. odd (m + n) ⇔ ¬(odd m ⇔ odd n)
⊦ ∀m n. odd (exp m n) ⇔ odd m ∨ n = 0
⊦ ∀m n. m ≤ n ∧ n ≤ m ⇔ m = n
⊦ ∀n l. n ≤ length l ⇒ length (take n l) = n
⊦ ∀n. odd n ⇔ ∃m. n = suc (2 * m)
⊦ ∀PAIR'. ∃fn. ∀a0 a1. fn (a0, a1) = PAIR' a0 a1
⊦ (null [] ⇔ T) ∧ ∀h t. null (h :: t) ⇔ F
⊦ ∀P Q. (∀x. P ⇒ Q) ⇔ (∃x. P) ⇒ ∀x. Q
⊦ ∀P Q. (∀x. P ∨ Q) ⇔ (∀x. P) ∨ ∀x. Q
⊦ ∀P Q. (∃x. P ∧ Q) ⇔ (∃x. P) ∧ ∃x. Q
⊦ ∀P Q. (∃x. P ⇒ Q) ⇔ (∀x. P) ⇒ ∃x. Q
⊦ ∀P Q. (∃x. P) ∧ (∃x. Q) ⇔ ∃x. P ∧ Q
⊦ ∀P Q. (∀x. P) ∨ (∀x. Q) ⇔ ∀x. P ∨ Q
⊦ ∀m n. m < n ⇔ ∃d. n = m + suc d
⊦ ∀P l. (∀x. member x l ⇒ P x) ⇔ all P l
⊦ ∀P l. (∃x. P x ∧ member x l) ⇔ exists P l
⊦ ∀<<. wellFounded << ⇔ ¬∃s. ∀n. << (s (suc n)) (s n)
⊦ ∀P. (∀x y. P x y) ⇔ ∀y x. P x y
⊦ ∀P. (∃x y. P x y) ⇔ ∃y x. P x y
⊦ bit0 0 = 0 ∧ ∀n. bit0 (suc n) = suc (suc (bit0 n))
⊦ ∀h t. last (h :: t) = (if t = [] then h else last t)
⊦ ∀P Q. (∀x. P ⇒ Q x) ⇔ P ⇒ ∀x. Q x
⊦ ∀P Q. (∀x. P ∨ Q x) ⇔ P ∨ ∀x. Q x
⊦ ∀P Q. (∃x. P ∧ Q x) ⇔ P ∧ ∃x. Q x
⊦ ∀P Q. (∃x. P ⇒ Q x) ⇔ P ⇒ ∃x. Q x
⊦ ∀P Q. P ∧ (∀x. Q x) ⇔ ∀x. P ∧ Q x
⊦ ∀P Q. P ∧ (∃x. Q x) ⇔ ∃x. P ∧ Q x
⊦ ∀P Q. P ⇒ (∀x. Q x) ⇔ ∀x. P ⇒ Q x
⊦ ∀P Q. P ⇒ (∃x. Q x) ⇔ ∃x. P ⇒ Q x
⊦ ∀P Q. P ∨ (∀x. Q x) ⇔ ∀x. P ∨ Q x
⊦ ∀P Q. P ∨ (∃x. Q x) ⇔ ∃x. P ∨ Q x
⊦ ∀m n. m < n ⇔ m ≤ n ∧ ¬(m = n)
⊦ ∀m n. even (exp m n) ⇔ even m ∧ ¬(n = 0)
⊦ ∀m n. ¬(m = 0) ⇒ m * n div m = n
⊦ ∀m n. ¬(m = 0) ⇒ m * n mod m = 0
⊦ ∀P Q. (∀x. P x ⇒ Q) ⇔ (∃x. P x) ⇒ Q
⊦ ∀P Q. (∀x. P x ∨ Q) ⇔ (∀x. P x) ∨ Q
⊦ ∀P Q. (∃x. P x ∧ Q) ⇔ (∃x. P x) ∧ Q
⊦ ∀P Q. (∃x. P x ⇒ Q) ⇔ (∀x. P x) ⇒ Q
⊦ ∀P Q. (∀x. P x) ∧ Q ⇔ ∀x. P x ∧ Q
⊦ ∀P Q. (∃x. P x) ∧ Q ⇔ ∃x. P x ∧ Q
⊦ ∀P Q. (∀x. P x) ⇒ Q ⇔ ∃x. P x ⇒ Q
⊦ ∀P Q. (∃x. P x) ⇒ Q ⇔ ∀x. P x ⇒ Q
⊦ ∀P Q. (∀x. P x) ∨ Q ⇔ ∀x. P x ∨ Q
⊦ ∀P Q. (∃x. P x) ∨ Q ⇔ ∃x. P x ∨ Q
⊦ ∀P. (∃!x. P x) ⇔ ∃x. ∀y. P y ⇔ x = y
⊦ ∀x y z. x = y ∧ y = z ⇒ x = z
⊦ ∀t1 t2 t3. t1 ∧ t2 ∧ t3 ⇔ (t1 ∧ t2) ∧ t3
⊦ ∀p q r. p ⇒ q ⇒ r ⇔ p ∧ q ⇒ r
⊦ ∀t1 t2 t3. t1 ∨ t2 ∨ t3 ⇔ (t1 ∨ t2) ∨ t3
⊦ ∀p q r. p ∧ q ⇒ r ⇔ p ⇒ q ⇒ r
⊦ ∀p q r. p ∧ q ⇒ r ⇔ q ⇒ p ⇒ r
⊦ ∀n x i. i < n ⇒ nth i (replicate n x) = x
⊦ ∀x y n. x ≤ y ⇒ exp x n ≤ exp y n
⊦ ∀m n p. m * (n * p) = m * n * p
⊦ ∀m n p. m + (n + p) = m + n + p
⊦ ∀m n p. exp m (n * p) = exp (exp m n) p
⊦ ∀m n p. m + n = m + p ⇔ n = p
⊦ ∀m n p. m + p = n + p ⇔ m = n
⊦ ∀m n p. m + n < m + p ⇔ n < p
⊦ ∀m n p. m + p < n + p ⇔ m < n
⊦ ∀m n p. m + n ≤ m + p ⇔ n ≤ p
⊦ ∀m n p. m + p ≤ n + p ⇔ m ≤ n
⊦ ∀m n p. m + n - (m + p) = n - p
⊦ ∀m n p. m + p - (n + p) = m - n
⊦ ∀m n p. (m * n + p) mod n = p mod n
⊦ ∀m n p. m < n ∧ n < p ⇒ m < p
⊦ ∀m n p. m < n ∧ n ≤ p ⇒ m < p
⊦ ∀m n p. m ≤ n ∧ n < p ⇒ m < p
⊦ ∀m n p. m ≤ n ∧ n ≤ p ⇒ m ≤ p
⊦ ∀l. ¬(l = []) ⇒ length (tail l) = length l - 1
⊦ ∀l m n. l @ m @ n = (l @ m) @ n
⊦ ∀P f l. all P (map f l) ⇔ all (P o f) l
⊦ ∀P f l. exists P (map f l) ⇔ exists (P o f) l
⊦ ∀f g l. map (g o f) l = map g (map f l)
⊦ ∀P x. (∀y. P y ⇔ y = x) ⇒ (select) P = x
⊦ ∀f g h. (f o (g o h)) = (f o g o h)
⊦ ∀P. (∀x. ∃y. P x y) ⇔ ∃y. ∀x. P x (y x)
⊦ ∀P. (∀x. ∃!y. P x y) ⇔ ∃!f. ∀x. P x (f x)
⊦ ∀t1 t2. (if T then t1 else t2) = t1 ∧ (if F then t1 else t2) = t2
⊦ ∀b f g. (λx. if b then f x else g x) = (if b then f else g)
⊦ ∀m n. 0 < m * n ⇔ 0 < m ∧ 0 < n
⊦ ∀m n. m * n = 0 ⇔ m = 0 ∨ n = 0
⊦ ∀m n. m + n = 0 ⇔ m = 0 ∧ n = 0
⊦ ∀l m. l @ m = [] ⇔ l = [] ∧ m = []
⊦ ∀p q. last (p @ q) = (if q = [] then last p else last q)
⊦ ∀l m. head (l @ m) = (if l = [] then head m else head l)
⊦ ∀P. (∀a. P (left a)) ∧ (∀a. P (right a)) ⇒ ∀x. P x
⊦ length [] = 0 ∧ ∀h t. length (h :: t) = suc (length t)
⊦ ∀l. ¬(l = []) ⇒ last l = nth (length l - 1) l
⊦ ∀P l x. member x (filter P l) ⇔ P x ∧ member x l
⊦ ∀f. injective f ⇔ ∀x1 x2. f x1 = f x2 ⇒ x1 = x2
⊦ ∀P. P 0 ∧ (∀n. P n ⇒ P (suc n)) ⇒ ∀n. P n
⊦ ∀P l. (∃x. exists (P x) l) ⇔ exists (λs. ∃x. P x s) l
⊦ ∀P l. (∀x. all (P x) l) ⇔ all (λs. ∀x. P x s) l
⊦ factorial 0 = 1 ∧ ∀n. factorial (suc n) = suc n * factorial n
⊦ (∀t. ¬¬t ⇔ t) ∧ (¬T ⇔ F) ∧ (¬F ⇔ T)
⊦ ∀NONE' SOME'. ∃fn. fn none = NONE' ∧ ∀a. fn (some a) = SOME' a
⊦ ∀m n. even (m - n) ⇔ m ≤ n ∨ (even m ⇔ even n)
⊦ ∀m n. ¬(n = 0) ⇒ (m div n = 0 ⇔ m < n)
⊦ ∀m n. ¬(n = 0) ⇒ m mod n mod n = m mod n
⊦ ∀n x. 0 < exp x n ⇔ ¬(x = 0) ∨ n = 0
⊦ ∀m n. exp m n = 0 ⇔ m = 0 ∧ ¬(n = 0)
⊦ ∀n l. n ≤ length l ⇒ length (drop n l) = length l - n
⊦ ∀n l. n ≤ length l ⇒ take n l @ drop n l = l
⊦ concat [] = [] ∧ ∀h t. concat (h :: t) = h @ concat t
⊦ ∀x l1 l2. member x (l1 @ l2) ⇔ member x l1 ∨ member x l2
⊦ ∀b t1 t2. (if b then t1 else t2) ⇔ (¬b ∨ t1) ∧ (b ∨ t2)
⊦ ∀p q r. p ∧ (q ∨ r) ⇔ p ∧ q ∨ p ∧ r
⊦ ∀p q r. (p ∨ q) ∧ r ⇔ p ∧ r ∨ q ∧ r
⊦ ∀m n i. i < n ⇒ nth i (interval m n) = m + i
⊦ ∀m n p. m * (n + p) = m * n + m * p
⊦ ∀m n p. m * (n - p) = m * n - m * p
⊦ ∀m n p. exp m (n + p) = exp m n * exp m p
⊦ ∀m n p. (m + n) * p = m * p + n * p
⊦ ∀m n p. (m - n) * p = m * p - n * p
⊦ ∀p m n. exp (m * n) p = exp m p * exp n p
⊦ ∀P l1 l2. filter P (l1 @ l2) = filter P l1 @ filter P l2
⊦ ∀P f l. filter P (map f l) = map f (filter (P o f) l)
⊦ ∀P l1 l2. all P (l1 @ l2) ⇔ all P l1 ∧ all P l2
⊦ ∀f l1 l2. map f (l1 @ l2) = map f l1 @ map f l2
⊦ ∀f. (∀m. ∃l. map f l = m) ⇔ ∀y. ∃x. f x = y
⊦ (∃!) = λP. (∃) P ∧ ∀x y. P x ∧ P y ⇒ x = y
⊦ ∀b f x y. f (if b then x else y) = (if b then f x else f y)
⊦ ∀b f g x. (if b then f else g) x = (if b then f x else g x)
⊦ ∀m n. odd (m - n) ⇔ n < m ∧ ¬(odd m ⇔ odd n)
⊦ ∀x n. exp x n = 1 ⇔ x = 1 ∨ n = 0
⊦ ∀P. (∃!x. P x) ⇔ ∃x. P x ∧ ∀y. P y ⇒ y = x
⊦ ∀P. (∀n. (∀m. m < n ⇒ P m) ⇒ P n) ⇒ ∀n. P n
⊦ ∀P g h. ∃f. ∀x. f x = (if P x then f (g x) else h x)
⊦ ∀P Q. (∀x. P x ∧ Q x) ⇔ (∀x. P x) ∧ ∀x. Q x
⊦ ∀P Q. (∃x. P x ∨ Q x) ⇔ (∃x. P x) ∨ ∃x. Q x
⊦ ∀P Q. (∀x. P x ⇒ Q x) ⇒ (∀x. P x) ⇒ ∀x. Q x
⊦ ∀P Q. (∀x. P x ⇒ Q x) ⇒ (∃x. P x) ⇒ ∃x. Q x
⊦ ∀P Q. (∀x. P x) ∧ (∀x. Q x) ⇔ ∀x. P x ∧ Q x
⊦ ∀P Q. (∃x. P x) ∨ (∃x. Q x) ⇔ ∃x. P x ∨ Q x
⊦ ∀l x. member x l ⇔ ∃i. i < length l ∧ x = nth i l
⊦ ∀t. (λp. t p) = λ(x, y). t (x, y)
⊦ ∀e f. ∃fn. fn 0 = e ∧ ∀n. fn (suc n) = f (fn n) n
⊦ ∀e f. ∃!fn. fn 0 = e ∧ ∀n. fn (suc n) = f (fn n) n
⊦ ∀e f. ∃fn. fn 0 = e ∧ ∀n. fn (suc n) = f n (fn n)
⊦ ∀m n. ¬(n = 0) ⇒ m div n * n + m mod n = m
⊦ ∀m n. m * n = 1 ⇔ m = 1 ∧ n = 1
⊦ ∀P Q l. (∀x. P x ⇒ Q x) ⇒ all P l ⇒ all Q l
⊦ ∀P. (∃n. P n) ⇔ ∃n. P n ∧ ∀m. m < n ⇒ ¬P m
⊦ ∀P. P [] ∧ (∀a0 a1. P a1 ⇒ P (a0 :: a1)) ⇒ ∀x. P x
⊦ ∀<< <<<. (∀x y. << x y ⇒ <<< x y) ∧ wellFounded <<< ⇒ wellFounded <<
⊦ reverse [] = [] ∧ ∀l x. reverse (x :: l) = reverse l @ x :: []
⊦ ∀m n p. m * n = m * p ⇔ m = 0 ∨ n = p
⊦ ∀m n p. m * p = n * p ⇔ m = n ∨ p = 0
⊦ ∀x y n. exp x n = exp y n ⇔ x = y ∨ n = 0
⊦ ∀m n p. m * n ≤ m * p ⇔ m = 0 ∨ n ≤ p
⊦ ∀m n p. m * p ≤ n * p ⇔ m ≤ n ∨ p = 0
⊦ ∀x y n. exp x n ≤ exp y n ⇔ x ≤ y ∨ n = 0
⊦ ∀f l i. i < length l ⇒ nth i (map f l) = f (nth i l)
⊦ ∀P. (∃n. P n) ⇔ P ((minimal) P) ∧ ∀m. m < (minimal) P ⇒ ¬P m
⊦ (∀n. 0 + n = n) ∧ ∀m n. suc m + n = suc (m + n)
⊦ (∀m. m - 0 = m) ∧ ∀m n. m - suc n = pre (m - n)
⊦ ∀f g l. all (λx. f x = g x) l ⇒ map f l = map g l
⊦ ∀P Q l. all (λx. P x ⇒ Q x) l ∧ all P l ⇒ all Q l
⊦ ∀P Q l. all P l ∧ all Q l ⇔ all (λx. P x ∧ Q x) l
⊦ ∀f y l. member y (map f l) ⇔ ∃x. member x l ∧ y = f x
⊦ cond = λt t1 t2. select x. ((t ⇔ T) ⇒ x = t1) ∧ ((t ⇔ F) ⇒ x = t2)
⊦ ∀a b n. ¬(a = 0) ⇒ (n ≤ b div a ⇔ a * n ≤ b)
⊦ ∀m n p. ¬(p = 0) ⇒ m * (n div p) ≤ m * n div p
⊦ ∀m n p. m * n < m * p ⇔ ¬(m = 0) ∧ n < p
⊦ ∀m n p. m * p < n * p ⇔ m < n ∧ ¬(p = 0)
⊦ ∀x y n. exp x n < exp y n ⇔ x < y ∧ ¬(n = 0)
⊦ ∀x y n. x < y ∧ ¬(n = 0) ⇒ exp x n < exp y n
⊦ ∀m n p. ¬(m = 0) ∧ n < p ⇒ m * n < m * p
⊦ ∀m n p. ¬(p = 0) ∧ m ≤ n ⇒ m div p ≤ n div p
⊦ ∀m n p. ¬(p = 0) ∧ p ≤ m ⇒ n div m ≤ n div p
⊦ ∀a b n. ¬(a = 0) ∧ b ≤ a * n ⇒ b div a ≤ n
⊦ ∀m n. ¬(n = 0) ⇒ (m mod n = 0 ⇔ ∃q. m = q * n)
⊦ ∀INL' INR'. ∃fn. (∀a. fn (left a) = INL' a) ∧ ∀a. fn (right a) = INR' a
⊦ (∀x. replicate 0 x = []) ∧ ∀n x. replicate (suc n) x = x :: replicate n x
⊦ (∀n. 0 * n = 0) ∧ ∀m n. suc m * n = m * n + n
⊦ ∀h1 h2 t1 t2. h1 :: t1 = h2 :: t2 ⇔ h1 = h2 ∧ t1 = t2
⊦ ∀x y a b. (x, y) = (a, b) ⇔ x = a ∧ y = b
⊦ ∀A B C D. (A ⇒ B) ∧ (C ⇒ D) ⇒ A ∧ C ⇒ B ∧ D
⊦ ∀A B C D. (A ⇒ B) ∧ (C ⇒ D) ⇒ A ∨ C ⇒ B ∨ D
⊦ ∀A B C D. (B ⇒ A) ∧ (C ⇒ D) ⇒ (A ⇒ C) ⇒ B ⇒ D
⊦ ∀m n p q. m = n + q * p ⇒ m mod p = n mod p
⊦ ∀m n p q. m < n ∧ p < q ⇒ m * p < n * q
⊦ ∀m n p q. m < p ∧ n < q ⇒ m + n < p + q
⊦ ∀m n p q. m < p ∧ n ≤ q ⇒ m + n < p + q
⊦ ∀m n p q. m ≤ n ∧ p ≤ q ⇒ m * p ≤ n * q
⊦ ∀m n p q. m ≤ p ∧ n < q ⇒ m + n < p + q
⊦ ∀m n p q. m ≤ p ∧ n ≤ q ⇒ m + n ≤ p + q
⊦ ∀m a b. (∀y. measure m y a ⇒ measure m y b) ⇔ m a ≤ m b
⊦ ∀P. (∀x. ∃!y. P x y) ⇔ ∃f. ∀x y. P x y ⇔ f x = y
⊦ ∀n h t. nth n (h :: t) = (if n = 0 then h else nth (n - 1) t)
⊦ ∀n. (∃k m. odd m ∧ n = exp 2 k * m) ⇔ ¬(n = 0)
⊦ (∀m. interval m 0 = []) ∧
∀m n. interval m (suc n) = m :: interval (suc m) n
⊦ (∀m. exp m 0 = 1) ∧ ∀m n. exp m (suc n) = m * exp m n
⊦ ∀l n. length l = suc n ⇔ ∃h t. l = h :: t ∧ length t = n
⊦ ∀P c x y. P (if c then x else y) ⇔ (c ⇒ P x) ∧ (¬c ⇒ P y)
⊦ (∀l. drop 0 l = l) ∧ ∀n h t. drop (suc n) (h :: t) = drop n t
⊦ ∀NIL' CONS'.
∃fn. fn [] = NIL' ∧ ∀a0 a1. fn (a0 :: a1) = CONS' a0 a1 (fn a1)
⊦ ∀m n p. ¬(n = 0) ⇒ m * (p mod n) mod n = m * p mod n
⊦ ∀m n p. ¬(n = 0) ⇒ m mod n * p mod n = m * p mod n
⊦ ∀m n p. ¬(n = 0) ⇒ exp (m mod n) p mod n = exp m p mod n
⊦ ∀m n p. ¬(m * p = 0) ⇒ m * n div (m * p) = n div p
⊦ ∀m n p. ¬(n * p = 0) ⇒ m div n div p = m div (n * p)
⊦ ∀m n p. ¬(n * p = 0) ⇒ m mod (n * p) mod n = m mod n
⊦ ∀m n p. ¬(p = 0) ∧ m + p ≤ n ⇒ m div p < n div p
⊦ ∀m n. (∃q. m = n * q) ⇔ (if n = 0 then m = 0 else m mod n = 0)
⊦ ∀n l i. n ≤ length l ∧ i < n ⇒ nth i (take n l) = nth i l
⊦ ∀P. (∃!x. P x) ⇔ (∃x. P x) ∧ ∀x x'. P x ∧ P x' ⇒ x = x'
⊦ ∀<<. wellFounded << ⇔ ∀P. (∀x. (∀y. << y x ⇒ P y) ⇒ P x) ⇒ ∀x. P x
⊦ (∀m. m < 0 ⇔ F) ∧ ∀m n. m < suc n ⇔ m = n ∨ m < n
⊦ (∀b f. case b f none = b) ∧ ∀b f a. case b f (some a) = f a
⊦ ∀m n q r. m = q * n + r ∧ r < n ⇒ m div n = q
⊦ ∀m n q r. m = q * n + r ∧ r < n ⇒ m mod n = r
⊦ ∀P Q l. (∀x. member x l ∧ P x ⇒ Q x) ∧ all P l ⇒ all Q l
⊦ ∀P Q l. (∀x. member x l ∧ P x ⇒ Q x) ∧ exists P l ⇒ exists Q l
⊦ ∀f l1 l2 n. length l1 = n ∧ length l2 = n ⇒ length (zipWith f l1 l2) = n
⊦ (∀l. [] @ l = l) ∧ ∀h t l. (h :: t) @ l = h :: t @ l
⊦ ∀a b n. ¬(a = 0) ⇒ (b div a ≤ n ⇔ b < a * (n + 1))
⊦ ∀<<. wellFounded << ⇔ ∀P. (∃x. P x) ⇔ ∃x. P x ∧ ∀y. << y x ⇒ ¬P y
⊦ ∀<<. wellFounded << ⇔ ∀P. (∃x. P x) ⇒ ∃x. P x ∧ ∀y. << y x ⇒ ¬P y
⊦ ∀t1 t2. (¬(t1 ∧ t2) ⇔ ¬t1 ∨ ¬t2) ∧ (¬(t1 ∨ t2) ⇔ ¬t1 ∧ ¬t2)
⊦ (∀l. take 0 l = []) ∧ ∀n h t. take (suc n) (h :: t) = h :: take n t
⊦ (∀P. all P [] ⇔ T) ∧ ∀h P t. all P (h :: t) ⇔ P h ∧ all P t
⊦ (∀P. exists P [] ⇔ F) ∧ ∀h P t. exists P (h :: t) ⇔ P h ∨ exists P t
⊦ (∀f. map f [] = []) ∧ ∀f h t. map f (h :: t) = f h :: map f t
⊦ (∀h. last (h :: []) = h) ∧ ∀h k t. last (h :: k :: t) = last (k :: t)
⊦ ∀b A B C D.
(A ⇒ B) ∧ (C ⇒ D) ⇒ (if b then A else C) ⇒ (if b then B else D)
⊦ ∀m n p. ¬(n = 0) ⇒ m mod n * (p mod n) mod n = m * p mod n
⊦ ∀a b n. ¬(n = 0) ⇒ (a mod n + b mod n) mod n = (a + b) mod n
⊦ ∀m n p. ¬(m * p = 0) ⇒ m * n mod (m * p) = m * (n mod p)
⊦ ∀m n p. ¬(n * p = 0) ⇒ m div n mod p = m mod (n * p) div n
⊦ ∀k l m.
nth k (l @ m) =
(if k < length l then nth k l else nth (k - length l) m)
⊦ (∀x. member x [] ⇔ F) ∧ ∀h x t. member x (h :: t) ⇔ x = h ∨ member x t
⊦ (∀m. m ≤ 0 ⇔ m = 0) ∧ ∀m n. m ≤ suc n ⇔ m = suc n ∨ m ≤ n
⊦ (∀h t. nth 0 (h :: t) = h) ∧ ∀h t n. nth (suc n) (h :: t) = nth n t
⊦ (∀b f. case b f [] = b) ∧ ∀b f h t. case b f (h :: t) = f h t
⊦ ∀t. ((T ⇔ t) ⇔ t) ∧ ((t ⇔ T) ⇔ t) ∧ ((F ⇔ t) ⇔ ¬t) ∧ ((t ⇔ F) ⇔ ¬t)
⊦ ∀l m.
length l = length m ∧ (∀i. i < length l ⇒ nth i l = nth i m) ⇒ l = m
⊦ ∀n l i.
n ≤ length l ∧ i < length l - n ⇒ nth i (drop n l) = nth (n + i) l
⊦ ∀n. (even n ⇒ ∃m. n = 2 * m) ∧ (¬even n ⇒ ∃m. n = suc (2 * m))
⊦ ∀P. (∃x. P x) ∧ (∃M. ∀x. P x ⇒ x ≤ M) ⇔ ∃m. P m ∧ ∀x. P x ⇒ x ≤ m
⊦ ∀f. (∀l m. map f l = map f m ⇒ l = m) ⇔ ∀x y. f x = f y ⇒ x = y
⊦ ∀m n q r. m = q * n + r ∧ r < n ⇒ m div n = q ∧ m mod n = r
⊦ ∀a b c d. ¬(b = 0) ∧ b * c < (a + 1) * d ⇒ c div d ≤ a div b
⊦ (∀P. filter P [] = []) ∧
∀h P t. filter P (h :: t) = (if P h then h :: filter P t else filter P t)
⊦ ∀P. (∀m n. P m n ⇔ P n m) ∧ (∀m n. m ≤ n ⇒ P m n) ⇒ ∀m n. P m n
⊦ ∀t. (T ∧ t ⇔ t) ∧ (t ∧ T ⇔ t) ∧ (F ∧ t ⇔ F) ∧ (t ∧ F ⇔ F) ∧ (t ∧ t ⇔ t)
⊦ ∀t. (T ∨ t ⇔ T) ∧ (t ∨ T ⇔ T) ∧ (F ∨ t ⇔ t) ∧ (t ∨ F ⇔ t) ∧ (t ∨ t ⇔ t)
⊦ ∀t. (T ⇒ t ⇔ t) ∧ (t ⇒ T ⇔ T) ∧ (F ⇒ t ⇔ T) ∧ (t ⇒ t ⇔ T) ∧ (t ⇒ F ⇔ ¬t)
⊦ ∀x m n.
exp x m = exp x n ⇔ (if x = 0 then m = 0 ⇔ n = 0 else x = 1 ∨ m = n)
⊦ ∀x m n.
exp x m ≤ exp x n ⇔ (if x = 0 then m = 0 ⇒ n = 0 else x = 1 ∨ m ≤ n)
⊦ (∀f. zipWith f [] [] = []) ∧
∀f h1 h2 t1 t2.
zipWith f (h1 :: t1) (h2 :: t2) = f h1 h2 :: zipWith f t1 t2
⊦ ∀x m n. exp x m < exp x n ⇔ 2 ≤ x ∧ m < n ∨ x = 0 ∧ ¬(m = 0) ∧ n = 0
⊦ ∀R.
(∀x y z. R x y ∧ R y z ⇒ R x z) ⇒
((∀m n. m < n ⇒ R m n) ⇔ ∀n. R n (suc n))
⊦ ∀R.
(∀x y z. R x y ∧ R y z ⇒ R x z) ∧ (∀n. R n (suc n)) ⇒
∀m n. m < n ⇒ R m n
⊦ ∀H.
(∀f g n. (∀m. m < n ⇒ f m = g m) ⇒ H f n = H g n) ⇒ ∃f. ∀n. f n = H f n
⊦ ∀a b c d. b * c < (a + 1) * d ∧ a * d < (c + 1) * b ⇒ a div b = c div d
⊦ ∀P.
(∀m. P m m) ∧ (∀m n. P m n ⇔ P n m) ∧ (∀m n. m < n ⇒ P m n) ⇒
∀m y. P m y
⊦ ∀m n p.
m * n = n * m ∧ m * n * p = m * (n * p) ∧ m * (n * p) = n * (m * p)
⊦ ∀m n p.
m + n = n + m ∧ m + n + p = m + (n + p) ∧ m + (n + p) = n + (m + p)
⊦ ∀<< <<<.
wellFounded << ∧ wellFounded <<< ⇒
wellFounded (λ(x1, y1) (x2, y2). << x1 x2 ∧ <<< y1 y2)
⊦ ∀a b n.
¬(n = 0) ⇒
((a + b) mod n = a mod n + b mod n ⇔ (a + b) div n = a div n + b div n)
⊦ ∀<<.
wellFounded << ⇒
∀H.
(∀f g x. (∀z. << z x ⇒ f z = g z) ⇒ H f x = H g x) ⇒
∃f. ∀x. f x = H f x
⊦ ∀<<.
wellFounded << ⇒
∀H.
(∀f g x. (∀z. << z x ⇒ f z = g z) ⇒ H f x = H g x) ⇒
∃!f. ∀x. f x = H f x
⊦ ∀<<.
(∀H.
(∀f g x. (∀z. << z x ⇒ f z = g z) ⇒ H f x = H g x) ⇒
∃f. ∀x. f x = H f x) ⇒ wellFounded <<
⊦ ∀R S.
wellFounded R ∧ wellFounded S ⇒
wellFounded (λ(r1, s1) (r2, s2). R r1 r2 ∨ r1 = r2 ∧ S s1 s2)
⊦ ∀R.
(∀x. R x x) ∧ (∀x y z. R x y ∧ R y z ⇒ R x z) ⇒
((∀m n. m ≤ n ⇒ R m n) ⇔ ∀n. R n (suc n))
⊦ ∀R.
(∀x. R x x) ∧ (∀x y z. R x y ∧ R y z ⇒ R x z) ∧ (∀n. R n (suc n)) ⇒
∀m n. m ≤ n ⇒ R m n
⊦ (∀n. 0 + n = n) ∧ (∀m. m + 0 = m) ∧ (∀m n. suc m + n = suc (m + n)) ∧
∀m n. m + suc n = suc (m + n)
⊦ ∀R S.
wellFounded R ∧ (∀a. wellFounded (S a)) ⇒
wellFounded (λ(r1, s1) (r2, s2). R r1 r2 ∨ r1 = r2 ∧ S r1 s1 s2)
⊦ ∀p q r.
(p ∧ q ⇔ q ∧ p) ∧ ((p ∧ q) ∧ r ⇔ p ∧ q ∧ r) ∧ (p ∧ q ∧ r ⇔ q ∧ p ∧ r) ∧
(p ∧ p ⇔ p) ∧ (p ∧ p ∧ q ⇔ p ∧ q)
⊦ ∀p q r.
(p ∨ q ⇔ q ∨ p) ∧ ((p ∨ q) ∨ r ⇔ p ∨ q ∨ r) ∧ (p ∨ q ∨ r ⇔ q ∨ p ∨ r) ∧
(p ∨ p ⇔ p) ∧ (p ∨ p ∨ q ⇔ p ∨ q)
⊦ ∀<<.
wellFounded << ⇒
∀H S.
(∀f g x.
(∀z. << z x ⇒ f z = g z ∧ S z (f z)) ⇒
H f x = H g x ∧ S x (H f x)) ⇒ ∃f. ∀x. f x = H f x
⊦ ∀<<.
wellFounded << ⇒
∀H.
(∀f g x. (∀z. << z x ⇒ f z = g z) ⇒ H f x = H g x) ⇒
∀f g. (∀x. f x = H f x) ∧ (∀x. g x = H g x) ⇒ f = g
⊦ ∀<<.
(∀H.
(∀f g x. (∀z. << z x ⇒ (f z ⇔ g z)) ⇒ (H f x ⇔ H g x)) ⇒
∀f g. (∀x. f x ⇔ H f x) ∧ (∀x. g x ⇔ H g x) ⇒ f = g) ⇒
wellFounded <<
⊦ (∀n. 0 * n = 0) ∧ (∀m. m * 0 = 0) ∧ (∀n. 1 * n = n) ∧ (∀m. m * 1 = m) ∧
(∀m n. suc m * n = m * n + n) ∧ ∀m n. m * suc n = m + m * n
⊦ (∀n. ¬(n = 0) ⇒ 0 < n) ∧ (∀n. ¬(n = 0) ⇒ 1 ≤ n) ∧
(∀n. 0 < n ⇒ ¬(n = 0)) ∧ (∀n. 0 < n ⇒ 1 ≤ n) ∧ (∀n. 1 ≤ n ⇒ 0 < n) ∧
∀n. 1 ≤ n ⇒ ¬(n = 0)
⊦ ∀<< P G H.
wellFounded << ∧
(∀f g x.
(∀z. << z x ⇒ f z = g z) ⇒
(P f x ⇔ P g x) ∧ G f x = G g x ∧ H f x = H g x) ∧
(∀f g x. (∀z. << z x ⇒ f z = g z) ⇒ H f x = H g x) ∧
(∀f x y. P f x ∧ << y (G f x) ⇒ << y x) ⇒
∃f. ∀x. f x = (if P f x then f (G f x) else H f x)